Nitrosamines and Polycyclic Aromatic Hydrocarbons in Smoke-Cured Bacon (Larou) of Artisanal and Industrial Origin - Lei Chen; Rui Liu; Mangang Wu; Hai Yu; Qingfeng Ge; Wangang Zhang (Foods, 2021)
The aim of this study was to compare the nitrosamines (NAs) and polycyclic aromatic hydrocarbons (PAHs) of Chinese smoke-cured bacon (Larou) of artisanal and industrial origin. The results showed that the average pH and Aw values of family-made Larou products were lower than those of industrial Larou, which was opposite to the TBARS level. The contents of residual nitrite and PAH4 in two artisanal Larou were significantly higher than those of the other groups (p < 0.05). The highest NA content (10.78 μg/kg) was found in family-made Larou. A correlation analysis indicated that the relationships between residual nitrite contents and total PAH8 contents (τ = 0.692, p < 0.01) and total NAs contents (τ = 0.805, p < 0.01) were characterized with a positive correlation. A principal component analysis indicated that the Larou from the industrial sources had similar safety attributes, and was more stable than the Larou processed in an artisanal manner. Our data suggest that Larou produced in industrial conditions is suitable for consumption.